ANALISIS PENGARUH STRATEGI PEMASARAN, PELAYANAN DAN KELENGKAPAN PRODUK TERHADAP LOYALITAS KONSUMEN OMI (Minimarket kampus UINSU) - Camelia Maulidiyah; Aulia Nur Balqis; Bella Azkiya syahani (CV. KAMPUS AKADEMIK PUBLISING, 2026)
This study aims to analyze the influence of marketing strategy, service quality, and product availability on consumer loyalty at OMI (UINSU Campus Minimarket). This study used a qualitative descriptive approach with data collection techniques including interviews, observation, and documentation to obtain a comprehensive overview of OMI's marketing and service activities. The results indicate that marketing strategies, encompassing product, price, promotion, and location, play a crucial role in attracting consumer interest and loyalty. In terms of service, a friendly, responsive attitude, and ease of transactions provide a positive shopping experience, encouraging repeat purchases. Furthermore, a product availability tailored to the needs of UINSU students and academics is a key factor in maintaining consumer loyalty. Overall, appropriate marketing strategies, good service, and a complete product range have been shown to contribute to increasing OMI consumer loyalty. This research is expected to serve as an evaluation and reference for campus minimarket managers in increasing competitiveness and attracting business.